Nutrition in Infancy Volume 1 - Watson, Ronald Ross.; Grimble, George.; Preedy, Victor R.; Zibadi, Sherma. (Nutrition and Health, 2013)
Nutrition in Infancy: Volume 1 is a very useful resource for all clinicians treating and preventing nutritional problems in infants. This volume covers a wide range of topics that support wellness in infants through the prevention and treatment of infectious diseases, malnutrition, and developmental and genetic abnormalities. A variety of chapters deal with nutrients for infants with disabilities, surgery, and other special needs. Special emphasis is provided for clinicians treating the millions of children in developing countries whose death is promoted by undernutrition or malnutrition. The next sections discuss the health benefits of supplementation and breast feeding and methods to improve use of berast feeding and its duration. In Nutrition in Infancy: Volume 1, all of these facets of nutrition and nutritional therapy are covered in a precise and practical way. The latest developments in diagnostic procedures and nutritional support are also included. Written by a group of international experts, this volume is an indispensable new reference for clinicians with an interest in the nutrition and health of pregnant mothers and their infants.